Medição experimental de temperatura no torneamento da liga Ti-6Al- 4V utilizando o método do termopar ferramenta-peça - Cunha, Renato Nunes (2020)
Titanium and its alloys stand out due to their excellent properties, such as high mechanical strength for low relative weight, conservation of their mechanical strength at high temperatures and extraordinary resistance to corrosion. However, the material has characteristics that make it a difficult-to-cut material. Therefore, the study of the machinability for titanium alloys, such as high mechanical strength for a lower relative density in relation to steels, has an important role in understanding the tool wear which is affected by the high chip tool interface temperatures. Thus, this work aims to investigate the influence of the cutting parameters on the chip-tool interface temperature measured by the tool-piece thermocouple method on the external cylindrical turning of the Ti-6Al-4V alloy. The work also aims to develop a methodology for calibrating the system, one of the major problems for using the method. The cutting tool used was the K10 grade carbide in the form of a properly sharpened bar. The calibration of the tool-piece thermocouple system was performed on the experimental apparatus itself, using two different methodology. The results obtained in the calibration tests demonstrated a linear behavior in the relationship between temperature and voltage over the temperature range used in the calibration. In addition, calibration using the modified revolving tailstock centre and the developed pin have shown similar results. Cylindrical turning tests were performed in which the cutting parameters (cutting speed, feed and depth of cut) and the condition of lubrication (dry or MQL) were varied. The results obtained in this work show that the cutting parameters directly influence the temperatures and the cutting force.